Nanoscale ultrasound-switchable FRET based liposomes for near-infrared fluorescence imaging in optically turbid media - Zhang, Qimei; Morgan, Stephen P.; Mather, Melissa L. (Wiley-VCH Verlag, 2017)
A new approach to fluorescence imaging in optically turbid media centered on the use of nanoscale ultrasound-switchable FRET based liposome contrast agents is reported. Liposomes containing lipophilic carbocyanine dyes as FRET pairs with emission wavelengths located in the near-infrared window were prepared. The efficacy of FRET and self-quenching for liposomes with a range of fluorophore concentrations was first calculated from measurement of the liposome emission spectra. Exposure of the liposomes to ultrasound resulted in changes in the detected fluorescent signal, the nature of which depending on the fluorophores used, detection wavelength and the fluorophore concentration. Line scanning of a tube containing the contrast agents with 1 mm inner diameter buried at a depth of 1 cm in a heavily scattering tissue phantom demonstrated an improvement in image spatial resolution by a factor of 6.3 as compared with images obtained in the absence of ultrasound. Improvements were also seen in image contrast with the highest obtained being 9% for a liposome system containing FRET pairs. Overall the results obtained provide evidence of the potential the nanoscale ultrasound-switchable FRET based liposomes studied here have for in vivo fluorescence imaging.